A Method for Tracking Eye Movements in the Study of Attention Selectivity in Social Anxiety - Olga Sagalakova (Journal of Global Pharma Technology, 2017)
One of the key mechanisms of social anxiety is the distortion of the cognitive-perceptual activity. Cognitive-behavioral models of social anxiety, being the basis of anxiety disorder, determine the distortion of attention in regards to stimuli – social threats (by opposing types of disorders – vigilance or avoidance).. The eye movement tracking method enables assessing the bias of attention to stimuli – facial expressions in teenagers with a high and low level of social anxiety. The study included 30 test subjects aged 16-18. We used the eye tracker SMI RED 250 mobile tracking technology. The test subjects were divided into groups based on the results of the questionnaire of social anxiety and social phobia. We discovered signs of severer disorganization of the target activity during the perception of both presumptive positive and negative facial expressions (higher amplitude of saccadic movements as a deviation from target priorities and multitasking) and a prolonged fixation of attention on stimuli fragments with negative expression (average and maximum duration of fixations on the path of visual scanning). During the attribution of characteristics, we often found typical cognitive distortions, which are most significant in regards to the presumptive positive stimulus (the “happy face” condition was attributed negative characteristics and mistakes were made in determining the emotion).Eye movement registration would enable a more pinpoint and continuous measurement of attention. The eye-tracker method is very promising for the understanding of information processing in case of affective disorders. Eye movements are an indicator of clear attention and perception (zones of interest, fixation, duration and sustainability of fixations, saccadic movements, eye trajectory sequence, etc.).Keywords: Tracking eye movement method (“Eye Tracker”), Social anxiety disorder, Selectivity of attention, Vigilance and avoidance, Social threat, Facial expressions.